Barkhausen Noise Emission in Milled Surfaces - Neslusan, Miroslav; Hrabovsky, Tomas; Cillikova, Maria; Micietova, Anna (Communications - Scientific letters of the University of Zilina, 2015)
This paper deals with the non-destructive evaluation of surface made of roll bearing steel 100Cr6 after milling cycles via Barkhausen noise technique. The paper discusses magnetic anisotropy linked with the structure transformations with regard to variable flank wear of cutting tool. Effective value of Barkhausen noise (BN), Peak Position and Full Width at Half Maximum (FWHM) derived from the raw BN signals are compared with metallographic observations and residual stress profiles. Surface integrity is also expressed in term of surface roughness due to comparable BN sensitive layer and the height of surface roughness profile.